“Ideal childbirth”: medicalization and construction of a hospital delivery assistance script in Brazil in mid-20th century - Silva, Fernanda; Nucci, Marina; Nakano, Andreza Rodrigues; Teixeira, Luiz (Saúde e Sociedade, 2019)
In Brazil, childbirth practices underwent deep changes and an intense medicalization process, especially in the mid-twentieth century. Childbirth, which by then still mostly took place at home with midwives’ assistance, began to increasingly occur in hospitals, assisted by obstetricians with their own interventions, practices and routines. Based on the analysis of 31 articles published in Brazilian obstetrics scientific journals between the 1930s and 1970s, we sought to understand the ideas about the process of constructing an “ideal” routine for hospital delivery and the arguments that supported the consolidation of the physician’s role as the most qualified professional for childbirth care. The obstetricians’ discussion about a scripting of childbirth care, including interventions and obstetric practices that should be performed routinely, shed light on the early stages of the medicalization process of childbirth in Brazil. Justified by the medical duty of reducing time and pain of normal birth and to not let Nature “act alone”, the interventions were presented as the result of a new medical-scientific knowledge that would constitute the modern obstetrics.